Estimation of crop losses due to grey mildew disease of cotton caused by Ramularia areola - P. D. WANGIKAR, S. K. SHlVANKAR and (Indian Phytopathology, 2002)
A field trial was laid out on H-4 cotton (G. hirsutum L.) for assessment of losses caused due to grey mildew disease during 1986-87 and 1987-88 under natural conditions. The losses in boll bearing, boll size and yield of seed cotton were directly proportional to the disease intensity. Heavy defoliation (92.24 to 99.27%), less boll bearing (12.97 to 15.95 bolls/plant), lowest boll weight (2.33 to 2.78 g/boll) and lowest yield (535.88 kg/ha) were noted from untreated plots having severe disease intensity (43.09 to 46.60%). The per cent loss in yield of seed cotton in untreated plots ranged from 62.67 to 68.69 over treated plots. The qualitative characters of seed cotton were also significantly affected by the disease.